2009
DOI: 10.1016/j.ijimpeng.2009.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Further investigation on the dynamic compressive strength enhancement of concrete-like materials based on split Hopkinson pressure bar tests. Part I: Experiments

Abstract: Effects of the inertia-induced radial confinement on the dynamic increase factor (DIF) of a mortar specimen are investigated in split Hopkinson pressure bar (SHPB) tests. It is shown that axial strain acceleration is unavoidable in SHPB tests on brittle samples at high strain-rates although it can be reduced by the application of a wave shaper. By introducing proper measures of the strain-rate and axial strain acceleration, their correlations are established. In order to demonstrate the influence of inertia-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(153 citation statements)
references
References 25 publications
8
126
0
7
Order By: Relevance
“…shows numerical simulations for specimens with diameters of 12 mm and 20 mm. It can be seen that an increase in the specimen diameter while keeping the same length (6 mm) leads to an increase of DIF which agrees with previous research [8,27]. This clearly demonstrates that inertia has an effect on the dynamic response, which should not be considered as genuine strain-rate effect.…”
Section: -P4supporting
confidence: 90%
See 1 more Smart Citation
“…shows numerical simulations for specimens with diameters of 12 mm and 20 mm. It can be seen that an increase in the specimen diameter while keeping the same length (6 mm) leads to an increase of DIF which agrees with previous research [8,27]. This clearly demonstrates that inertia has an effect on the dynamic response, which should not be considered as genuine strain-rate effect.…”
Section: -P4supporting
confidence: 90%
“…The DIF of concrete-like materials in the high strain-rate range of 10 1 -10 3 s −1 is often obtained by performing dynamic test using a split Hopkinson pressure bar (SHPB); however, it has long been debated whether the increase of compressive strength observed in SHPB tests of unconfined specimens is an intrinsic material property or is related to structural or inertial effects [4][5][6]. It has been shown that the induced lateral confinement in SHPB test, which causes increase of DIF, may be caused by friction between the bars and the specimen [5,7], large specimen diameters [8,9], and radial inertia [10,11]. The enhanced DIF observed when the induced lateral confinement is present should not be related to material property and the SHPB data should be correctly interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the radial confinement induced by the axial strain acceleration can be reduced by reducing the SHPB specimen diameter or by the use of tubular SHPB specimen (Zhang et al 2009). Brace and Jones (1971) found that the rapid increase of compressive strength of rocks after a transition strain-rate can be interpreted by the change of stress state from uniaxial stress to uniaxial strain, representing increased radial confinement (Field et al 2004).…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…It was found by Zhang et al (2009) that the strain-rate at the moment of failure of the specimen in a SHPB test is closely correlated to the axial strain acceleration for both solid and tubular mortar specimens. Moreover, it was shown that the axial strain acceleration in a largediameter solid specimen is greater than that in a small-diameter specimen while the axial M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in employing pulse-shaping technique to determine the dynamic properties of concrete-like materials, aiming to attenuate high-frequency oscillations and increase the rise-time of the incident pulse, and achieve stress equilibrium and nearly constant strain-rate in the specimens (Chen, 2003;Duffy, 1971;Frew, 2002). Using the pulse-shaping SHPB apparatus, a large number of studies were conducted to investigate the dynamic mechanical properties of normal concrete (Zhang, 2009), high-strength concrete (Wang, 2012), and fiber-reinforced concrete , and so on. However, few studies have been reported to investigate the dynamic response of mortar to impact loading, although it is significant for the engineering applications, as stated above.…”
Section: Introductionmentioning
confidence: 99%